Interactions between ecological factors in the developmental environment modulate pupal and adult traits in a polyphagous fly. Issue 11 (26th April 2019) - Nguyen, Binh; Ponton, Fleur; Than, Anh; Taylor, Phillip W.; Chapman, Toni; Morimoto, Juliano
Abstract: In holometabolous insects, adult fitness depends on the quantity and quality of resource acquired at the larval stage. Diverse ecological factors can influence larval resource acquisition, but little is known about how these factors in the larval environment interact to modulate larval development and adult traits. Here, we addressed this gap by considering how key ecological factors of larval density, diet nutritional composition, and microbial growth interact to modulate pupal and adult traits in a polyphagous tephritid fruit fly, Bactrocera tryoni (aka "Queensland fruit fly"). Larvae were allowed to develop at two larval densities (low and high), on diets that were protein‐rich, standard, or sugar‐rich and prepared with or without preservatives to inhibit or encourage microbial growth, respectively. Percentage of adult emergence and adult sex ratio were not affected by the interaction between diet composition, larval density, and preservative treatments, although low preservative content increased adult emergence in sugar‐rich diets but decreased adult emergence in protein‐rich and standard diets. Pupal weight, male and female adult dry weight, and female (but not male) body energetic reserves were affected by a strong three‐way interaction between diet composition, larval density, and preservative treatment, whereby in general, low preservative content increased pupal weight and female lipid storage in sugar‐rich diets particularly at low‐larval density and differentially modulated the decrease in adult body weight caused by larval density across diets. Our findings provide insights into the ecological factors modulating larval development of a polyphagous fly species and shed light into the ecological complexity of the larval developmental environment in frugivorous insects. Abstract : Fitness of holometabolous insects depends on resource acquisition at the larval stage. We investigated how key ecological factors such as density, diet composition, and microbial growth affect larval and adult traits. The data demonstrate how these factors interact to determine the quality of the larval developmental environment.